1.6 Ga crustal thickening along the final Nuna suture - Pourteau, Amaury; Smit, M.; Li, Zheng-Xiang; Collins, W.; Nordsvan, A.; Volante, S.; Li, J. (Geological Society of America, 2018)
© 2018 Geological Society of America. The precise timing and nature of the final assembly of the supercontinent Nuna, marked by the collision of proto-Australia and Laurentia (North America) between 1.65 and 1.50 Ga, has remained elusive. The final Nuna suture has been speculated to be concealed in northeastern Australia, but univocal evidence for crustal thickening across the suture zone has been critically lacking. Here we report new garnet petrological and geochronological results of samples from both sides of the inferred suture. The precise garnet Lu-Hf dates show uniformly synchronous prograde metamorphism between 1606 Ma and 1598 Ma, representing crustal thickening in the Georgetown Inlier and simultaneous basin inversion in the Mount Isa Inlier. Broad-scale orogenesis is further supported by the asymmetrical bivergent thrust wedge imaged by deep seismic reflection in the northeastern Australia continental crust. The precisely dated collision-related processes in northeastern Australia correlate with 1.61-1.59 Ga orogenesis recorded within South Australia and North America, suggesting a large-scale collision of Laurentia with Australia-East Antarctica, and pinpointing the final assembly of the supercontinent Nuna.